Effectiveness of Mobile-Based Progressive and Fixed Physical Activity on Depression, Stress, Anxiety, and Quality of Life Outcomes Among Adults in South Korea: Randomized Controlled Trial - Ye Hoon Lee; Hyungsook Kim; Juhee Hwang; Sihyeon Noh (JMIR Publications, 2024)
BackgroundDepression acts as a significant obstacle to the overall well-being of individuals. Given the significant consequences, timely recognition and proactive steps to manage symptoms of depression become essential. Such actions not only reduce personal distress but also play a crucial role in reducing its far-reaching impact on society as a whole. ObjectiveIn response to this concern, the objective of this study was to explore the use of mobile-based interventions as a possible remedy. More specifically, this study aimed to investigate the effectiveness of 2 types of physical activity (PA), progressive and fixed, within a mobile-based app on depression, perceived stress, anxiety, physical health, and psychological health, aiming to contribute to the optimization of mental health benefits. MethodsParticipants (N=60; mean age 25.29, SD 6.10 years) were recruited using a combination of web-based and offline methods, and the study lasted for 8 weeks. The baseline and posttest questionnaires were administered to all participants. The participants were randomly assigned to 1 of the 3 groups: progressive group (n=20; performing mobile-based progressive PA), fixed group (n=20; performing mobile-based fixed intensity PA), and control group C (n=20). Data analysis involved comparing scores between the experimental and control groups using a one-way ANOVA, paired sample t tests (2-tailed), and repeated measures ANOVA with a 3 (group)×2 (time) design. ResultsThe findings revealed significant improvements in mental health indicators among participants engaged in both fixed and progressive PA groups compared with the control group. However, the fixed PA group demonstrated more significant reductions in symptoms. Specifically, the progressive PA group showed significant reductions in depression (F1,36=6.941; P=.01; ηp2=0.16) and perceived stress (F1,36=5.47; P=.03; ηp2=0.13), while the fixed PA group exhibited significant reductions in depression (F1,37=5.36; P=.03; ηp2=0.12), perceived stress (F1,37=7.81; P=.008; ηp2=0.17), and general anxiety disorder (F1,37=5.45; P=.03; ηp2=0.13) compared with the control group. ConclusionsThis study underscores the potential of mobile-based PA in improving mental health outcomes. The findings offer significant insights for mental health professionals and researchers aiming to optimize mental well-being through innovative mobile therapies. Trial RegistrationClinical Research Information Service KCT0009100; https://tinyurl.com/mr33fmur